Polyorchidism: a rare case report - Vasaiya, Mehulkumar K.; Shah, Samir M.; Gohil, Vikram B. (International Surgery Journal, 2020)
Polyorchidism is a very rare genitourinary anomaly defined with the presence of more than two testicles. Polyorchidism is associated up to 40% with undescended testicles. The present report is about an incidentally detected triorchidism case with left side, one atrophic and second Normal testis. A 4 years old child, diagnosed with left side undescended testis revealed during orchiopexy polyorchidism with distinct epididymis and vas deferens. Whereas one of the testis was in regular size, the other was atrophic. Orchidectomy was conducted on the atrophic testicle and sent for histopathological examination (HPE), orchiopexy to the normal size testicle. The atrophic testicle excised was referred histopathological analysis and was diagnosed as left side undescended atrophic testis. The patient discharged on 2nd postoperative day, was considering as normal during postoperative evaluation made on 5th postoperative day. Polyorchidism is a rare genitourinary abnormality, and its management is still controversial. Yet, we believe that orchidectomy is to be conducted in atrophic testicle cases.